Antiplasmodial potential and quantification of aloin and aloe-emodin in Aloe vera collected from different climatic regions of India - Sandeep Kumar; Manila Yadav; Amita Yadav; Pooja Rohilla; Jaya Parkash Yadav (BMC, 2017)
Abstract Background In this study, Aloe vera samples were collected from different climatic regions of India. Quantitative HPTLC (high performance thin layer chromatography) analysis of important anthraquinones aloin and aloe-emodin and antiplasmodial activity of crude aqueous extracts was done to estimate the effects of these constituents on antiplasmodial potential of the plant. Methods HPTLC system equipped with a sample applicator Linomat V with CAMAG sample syringe, twin rough plate development chamber (20 x 10 cm), TLC Scanner 3 and integration software WINCATS 1.4.8 was used for analysis of aloin and aloe-emodin amount. The antiplasmodial activity of plant extracts was assessed against a chloroquine (CQ) sensitive strain of P. falciparum (MRC-2). Minimum Inhibitory Concentration (MIC) of aqueous extracts of selected samples was determined according to the World Health Organization (WHO) recommended method that was based on assessing the inhibition of schizont maturation in a 96-well microtitre plate. EC (effective concentration) values of different samples were observed to predict antiplasmodial potential of the plant in terms of their climatic zones. Results A maximum quantity of aloin and aloe-emodin i.e. 0.45 and 0.27 mg/g respectively was observed from the 12 samples of Aloe vera. The inhibited parasite growth with EC50 values ranging from 0.289 to 1056 μg/ml. The antiplasmodial EC50 value of positive control Chloroquine was observed 0.034 μg/ml and EC50 values showed by aloin and aloe-emodin was 67 μg/ml and 22 μg/ml respectively. A positive correlation was reported between aloin and aloe-emodin. Antiplasmodial activity was increased with increase in the concentration of aloin and aloe-emodin. The quantity of aloin and aloe-emodin was decreased with rise in temperature hence it was negatively correlated with temperature. Conclusions The extracts of Aloe vera collected from colder climatic regions showed good antiplasmodial activity and also showed the presence of higher amount of aloin and aloe-emodin in comparison to collected from warmer climatic sites. Study showed significant correlation between quantities of both the anthraquinones used as marker compounds and EC50 values of the different Aloe vera extracts. Although, both the anthraquinones showed less antiplasmodial potential in comparison to crude extracts of different Aloe vera samples. Diverse climatic factors affect the quantity of tested compounds and antiplasmodial potential of the plant in different Aloe vera samples.